Handbook of Technical and Vocational Teacher Professional Development in the Digital Age - Han, Xibin; Zhou, Qian; Li, Ming; Wang, Yuping (SpringerBriefs in Education,, 2024)
This is an open access book. Covering both theories and practices in Technical Vocational Education and Training (TVET) teacher development, this book provides up-to-date discussions and recommendations on issues relating to TVET teacher development in the digital age. It caters for the needs of in-service teachers and trainers, as well as TVET leaders who want to upscale their professional learning and development in terms of vision, knowledge, expertise, and industry skills needed in the transition to the digital era. What is particularly useful to TVET teachers/trainers are the proposed competency development framework, competency indicators, and the assessment instrument. Drawing on extensive research regarding TVET teachers' competency development and today's industry needs, the proposed framework and indicators can be readily used to inform the self-assessment of one's professional competency level, so as to plan one's career trajectory accordingly.Teachers and trainers may also find the exemplary cases of teachers' professional development from various countries inspiring and motivating. The book also serves as a useful reference for TVET leaders, administrators and teacher trainers. The book's competency framework, indicators, and strategies are an adaptable reference for planning professional development policies, evaluation mechanisms, and programs for teachers.